2002
DOI: 10.1002/etc.5620210717
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of in vitro androgenic activity and the identification of environmental androgens in United Kingdom estuaries

Abstract: Environmental androgens are a group of compounds that to date have received very little attention. In this study, a yeast-based androgen screen (YAS) was used to determine the level of in vitro androgenic activity in seven United Kingdom estuaries. Surface water, sediment pore water, and sediment particulate material solvent extracts collected from Southampton Water, the Thames, Mersey, Tees, Tyne, Clyde, and Forth were tested for in vitro androgenic activity. Eleven of the 41 surface water samples collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 17 publications
4
79
0
Order By: Relevance
“…Although domestic effluent is suspected to have a high content of natural androgens, an advanced level of treatment, such as activated sludge systems, seems to be very efficient in removing androgenic compounds [30]. Wastewater effluent did not cause any significant androgenic effects on the reproductive parameters in stickleback, but it is important to remember that the effluent may have been androgenic but was not detected with the biomarkers used in the present study.…”
Section: Estrogenicity and Androgenicity In The Wastewater Effluentmentioning
confidence: 62%
“…Although domestic effluent is suspected to have a high content of natural androgens, an advanced level of treatment, such as activated sludge systems, seems to be very efficient in removing androgenic compounds [30]. Wastewater effluent did not cause any significant androgenic effects on the reproductive parameters in stickleback, but it is important to remember that the effluent may have been androgenic but was not detected with the biomarkers used in the present study.…”
Section: Estrogenicity and Androgenicity In The Wastewater Effluentmentioning
confidence: 62%
“…[16,17] Although no adverse effects on aquatic organisms have so far been associated with discharges in such effluents, a survey of effects in wastewaters is motivated. [19] It was found that androstenedione contributed to 36%, androstanedione 33%, androsterone and epiandrosterone together 14% and dehydrotestosterone to 15% of the in vitro androgenic activity in the effluent, respectively. [18] Untreated wastewaters contained from below the detection limit to 4300 ng DHT equivalents/L.…”
Section: Introductionmentioning
confidence: 97%
“…This fractionation approach is a non-selective and non-destructive clean-up methodology that aims to enable the identification of all biologically active compounds in the sample. EDA has successfully been applied to evaluate endocrine potencies in several water systems, such as waste-water treatment plants [1, 2], rivers [2, 3], harbor areas [4], marine sediment [5], and biota [6]. …”
Section: Introductionmentioning
confidence: 99%